Excitation of the wake waves by a laser pulse in ion dielectrics - Balakirev, V.A.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2020)
The process of excitation of Cherenkov electromagnetic radiation by a laser pulse in ion dielectric waveguide is investigated. Nonlinear electric polarization in isotropic ion dielectric medium and, accordingly, polarization charges and currents induced by a ponderomotive force of a laser pulse are determined. Frequency spectra of the excited wakefields in the infrared and microwave frequency ranges are obtained. The spatio-temporal structure of the wakefield in ion dielectric waveguide is obtained and studied. It is shown that the excited field consists of a potential polarization electric field, as well as a set of eigen electromagnetic waves of ion dielectric waveguide. Досліджено процес збудження черенковського електромагнітного поля лазерним імпульсом в іонному діелектричному хвилеводі. Показано, що збуджуване поле складається з потенціального поляризаційного електричного поля поздовжніх оптичних фононів та набору власних електромагнітних хвиль іонного діелектричного хвилеводу. Исследован процесс возбуждения черенковского электромагнитного излучения лазерным импульсом в ионном диэлектрическом волноводе. Показано, что возбуждаемое поле состоит из потенциального поляризационного электрического поля продольных оптических фононов и набора собственных электромагнитных волн ионного диэлектрического волновода.